2010
DOI: 10.1152/ajpgi.00445.2009
|View full text |Cite
|
Sign up to set email alerts
|

CCK-independent mTORC1 activation during dietary protein-induced exocrine pancreas growth

Abstract: JA. CCK-independent mTORC1 activation during dietary proteininduced exocrine pancreas growth. Am J Physiol Gastrointest Liver Physiol 299: G1154 -G1163, 2010. First published August 26, 2010 doi:10.1152/ajpgi.00445.2009.-Dietary protein can stimulate pancreatic growth in the absence of CCK release, but there is little data on the regulation of CCK-independent growth. To identify mechanisms whereby protein stimulates pancreatic growth in the absence of CCK release, C57BL/6 control and CCK-null male mice were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…As a CK2 flavonoid inhibitor, luteolin decreases the phosphorylation of serine residues and influences processes such as transcriptional regulation and signal transduction in cells[37], [38]. Consistent with previous studies, we found that pre-treatment with luteolin reduced the ΔFosB protein level in the CPu and the locomotor activity of mice sensitized by MA.…”
Section: Discussionsupporting
confidence: 91%
“…As a CK2 flavonoid inhibitor, luteolin decreases the phosphorylation of serine residues and influences processes such as transcriptional regulation and signal transduction in cells[37], [38]. Consistent with previous studies, we found that pre-treatment with luteolin reduced the ΔFosB protein level in the CPu and the locomotor activity of mice sensitized by MA.…”
Section: Discussionsupporting
confidence: 91%
“…2A and B). We next queried whether endogenous GLP-1R signaling was required for the adaptive increase in pancreatic mass in response to an HPD (20); however, pancreas weight was increased to a similar extent in HPD-fed Glp1r +/+ versus Glp1r 2/2 mice (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…A high-protein (40%) diet can induce pancreas growth in mice, independent of cholecystokinin (CCK). 39 Other studies have shown that AAs can increase pancreatic trypsin levels and stimulate pancreas growth, 40 , 41 and the AA leucine, specifically, modulates growth responses of pancreatic progenitors, involving mTORC1. 42 , 43…”
mentioning
confidence: 98%